Synthesis and structure of 2,8-dimethyl-10,10-dichlorophenoxatellurine - Mostaghimi Farzin (De Gruyter, 2021)
The condensation of 4,4’-dimethyldiphenylether with tellurium tetrachloride yielded 2,8-dimethyl-10,10-dichlorophenoxatellurine (3), which was characterized by X-ray diffraction. Unlike the parent phenoxatellurine (1) and the 10,10,-dichlorophenoxatellurine (2) showing butterfly conformations, 3 reveals a planar ring structure.